Performance comparison of maceration method, soxhletation method, and microwave-assisted extraction in extracting active compounds from soursop leaves (Annona muricata): A review. Issue 1 (March 2021) - Tambun, R; Alexander, V; Ginting, Y
Abstract: Soursop ( Annona muricata ) is a plant that is widely available in Indonesia. Of all parts of the soursop plant, the leaves are the most interesting parts to be studied. Soursop leaves are the most interesting part to be investigated because soursop leaves have many benefits and benefits that have been applied in the health sector, both traditional and modern. This is because soursop leaves contain many active compounds such as alkaloids, terpenoids, flavonoids, tannins, saponins, acetogenins, and others. The purpose of this review is to compare the best methods commonly used to extract active compounds from soursop leaves. The methods studied were maceration, soxhletation and microwave assisted extraction (MAE). The mechanism of the extraction processes and the percentage of yield achieved from the three methods are also reviewed. The results of the review show that MAE is the method that produces the highest yield of the three methods with a yield of 33.98%. This method also has another advantage that is a shorter extraction time.